ANONIM XATLARDA NOADABIY LEKSIK UNSURLARNING VOQELANISH TURLARI VA XUSUSIYATLARI - Yoqubova, S. (SCIENCE and SOCIETY, 2024)
In linguistics, non-literary lexical elements are studied in vocabulary with a limited scope of use. A number of studies have been carried out on the linguistic nature of lexemes in this group. The question of the concept of a non-literary lexical element, its role and meaning is relevant in linguistic examination. The article, based on examples, shows a non-literary lexical element, its meaning, as well as factors associated with its appearance in speech.